An Analysis of Students’ Learning Styles on Microbiology Lectures in the New Normal Era - Roberi Sepda Fian Sinaga; Hasruddin Hasruddin; Fauziyah Harahap (Publikasi Indonesia, 2021)
The aim of this study was to analyze the learning styles on microbiology lectures for students in the new normal era. This study was a non-experimental with quantitative data. The population were all the third semester students majoring in Biology, Universitas Negeri Medan who studied microbiology consisting of 6 classes totaling 180 people. The sample consisted of 3 classes of 60 people who were taken randomly using random sampling technique. The data analysis technique was carried out using inferential statistics. The results showed that students’ visual learning style obtained 71%, audio learning style obtained 64% in the good category and kinesthetic learning style obtained 63% were all in the good category. Of the three learning styles, the highest percentage was found in the visual learning style.